2004
DOI: 10.1073/pnas.0401500101
|View full text |Cite
|
Sign up to set email alerts
|

CD4 on CD8+T cells directly enhances effector function and is a target for HIV infection

Abstract: Costimulation of purified CD8 ؉ T lymphocytes induces de novo expression of CD4, suggesting a previously unrecognized function for this molecule in the immune response. Here, we report that the CD4 molecule plays a direct role in CD8 ؉ T cell function by modulating expression of IFN-␥ and Fas ligand, two important CD8 ؉ T cell effector molecules. CD4 expression also allows infection of CD8 cells by HIV, which results in down-regulation of the CD4 molecule and impairs the induction of IFN-␥, Fas ligand, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
58
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 54 publications
6
58
0
2
Order By: Relevance
“…Our data suggest that, after cellular activation, a subset of CD8 ϩ T cells are induced to express CD4. We have previously determined that the newly expressed CD4 on human CD8 ϩ T cell modulates CTL, FasL, and IFN-␥ responses after ligation in vitro (9). Our current studies suggest that CD4 enhances the CD8 ϩ T cell response against viral and alloantigens in vivo through a similar mechanism.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Our data suggest that, after cellular activation, a subset of CD8 ϩ T cells are induced to express CD4. We have previously determined that the newly expressed CD4 on human CD8 ϩ T cell modulates CTL, FasL, and IFN-␥ responses after ligation in vitro (9). Our current studies suggest that CD4 enhances the CD8 ϩ T cell response against viral and alloantigens in vivo through a similar mechanism.…”
Section: Discussionsupporting
confidence: 50%
“…In most cases, the rise in the percentage of CD8 ϩ CD4 ϩ cells appears to be a direct result of cellular activation, with these cells displaying a phenotype of activated or previously activated T cells. We and others have previously shown that costimulation of human CD8 ϩ T cells results in the de novo expression of CD4, consistent with the activated phenotype seen in vivo (9)(10)(11)(12)(13).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…that there is de novo expression of CD4 on CD8 cells after activation and in HIV-positive individuals, 0.7-3.3% of CD8 ϩ T cells are double positive and most of these cells are in the memory subset (28,29). A population of CD4 ϩ CD8 ϩ double positive T cells has been identified as effector memory cells, is shown to control viral replication in hepatitis C virus-infected individuals and is commonly found as memory populations in other species (30,31).…”
Section: Figurementioning
confidence: 99%